2013
DOI: 10.1063/1.4798347
|View full text |Cite
|
Sign up to set email alerts
|

The role of charge and ionic radius on fission product segregation to a model UO2 grain boundary

Abstract: The segregation energies of a range of fission products in UO2 to a Σ5 symmetric tilt grain boundary have been calculated using empirical potentials and their dependency on site, charge, and ionic radius has been determined. Density functional theory calculations provide information about the detailed bonding environment around the segregates. While most of the fission products prefer to reside in sites with large free volume, there are some that form strong bonds with neighboring oxygen ions, and thus prefer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…However, we find that ionic valence has a somewhat stronger influence on the dopant segregation as compared to ionic size. Hong et al [48] reported the segregation energies of several fission products to a UO2 grain boundary and attributed the prepensity of segregation to ionic charge, ionic radius, and the particular segregation site. Analogous to the trend reported here, they found that fission products with similar ionic charge as the host uranium ion exhibit weaker segregation, while those with dissimilar ionic charge segregate more strongly.…”
Section: Discussionmentioning
confidence: 99%
“…However, we find that ionic valence has a somewhat stronger influence on the dopant segregation as compared to ionic size. Hong et al [48] reported the segregation energies of several fission products to a UO2 grain boundary and attributed the prepensity of segregation to ionic charge, ionic radius, and the particular segregation site. Analogous to the trend reported here, they found that fission products with similar ionic charge as the host uranium ion exhibit weaker segregation, while those with dissimilar ionic charge segregate more strongly.…”
Section: Discussionmentioning
confidence: 99%
“…Nerikar et al attempted to map the Xe segregation properties onto the strain obtained from atomistic simulations, but, although some correlation was found, it was difficult to quantitatively predict the segregation energy from the local strain [42]. This may be related to the importance of electrostatic effects in these systems [55]. Fig.…”
Section: Segregation Datamentioning
confidence: 99%
“…Capabilities of the picosecond acoustic can be further expanded by taking into consideration recent reports where the structure of interface resulted in additional modifications to the Brillouin oscillations, (31,37) such as modulation in amplitude and emergence of a phase lag 12 upon propagation through a distinct layer. We speculate that these effects can be leveraged to study impurity segregation at grain boundaries using picosecond ultrasonics.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, grain boundaries attract impurities and other defects that have further implications on determining material behavior. (12) Additionally the boundaries themselves undergo motion under external stimuli such as mechanical deformation, radiation and high temperatures. (7,13) Grain boundary motion and the associated change in crystal misorientation across the boundary can significantly influence transport and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%